Young Generation’s Interest in Organic Agriculture : Its Effect on The Development of Organic Rice Cultivation in Ngemplak District, Sleman District, DI.Yogyakarta - Asih Farmia (Gontor AGROTECH Science Journal, 2020)
The purpose of the study  knowing the interest of the young generation in the organic agriculture field, its effect on the development of organic rice cultivation in Ngemplak Subdistrict, Sleman Regency, Yogyakarta Special Region which was held from May to August 2020 in Widodomartani Village. The location was determined purposively because it has organic farmer groups and livestock groups. The samples were determined purposively, namely the young generation aged 16-35 years. Sampling was selected by simple random sampling. Determination of the number of samples using the Slovin formula. Data analysis was performed by qualitative descriptive analysis, the results of which were presented in tabulated form. To measure the interest of the young generation, measured using the Likert Scale Technique. From the analysis, it is known that the young generation's interest in organic farming is classified as less interested in the agroinput sub-system with an average score of 2.45 (61.25%), the cultivation sub-system with an average score of 2.27 (61.82%). ) and the marketing sub-system with an average score of 2.46 (61.47%). This is because they consider agriculture to be a job that is not promising and dirty and tiring so that the number of organic farmers in Widodomartani Village has not increased, even though organic rice production has increased since 2017. The efforts and roles of related parties such as government, businessmen, private sector and organic practitioners are very much  needed to attract young people to engage in organic agriculture.